CURRENT ISSUES IN PRESERVATION OF RECREATIONAL PTENTIAL OF KYIV REGION - Poltavets, A. M. (Землеустрій, кадастр і моніторинг земель, 2013)
Current situation and usage of recreational lands of the Kyiv region is investigated. Research of ways to preserve and disclose the recreational   potential of the region is done.